Quality systems for tourism in protected areas and their application to the pastures of Pohorje - Lešnik Štuhec, Tanja (Academica turistica, 2016)
The systematic integration of agricultural and tourism products and services from the pastures of Pohorje under the "From Pohorje" brand ensures consistent quality in both a bottom-up and top-downmanner. The stakeholders were involved in (i) three regional workshops, which involved analysis of the supply and demand for general products and services, as well as tourism products, in conjunction with Pohorje's environmentally protected area; (ii) a fourth workshop for establishing supply chains and a marketing approach, and (iii) a fifth workshop for designing action plans for product providers in conjunction with Pohorje pastures. Guidelines have been developed within the alpa project for ensuring quality and establishing supply chains and marketing for products, tourism services and tourism products in addition to 20 action plans for providers in conjunction with the Pohorje pastures. The pastures represent an excellent starting point for an eco-destination on Pohorje that offers unique experiences. The quality of all products and services must be comprehensively planned, implemented and evaluated. Promoting networking for integration and establishing organized supply chains can provide a criticalmass of quality products from and experiences of the Pohorje pastures. Systematic, strategic and operative marketing of the destination ensures that products have a certain "homey" feel, and are targeted at specific groups. Pohorje Vision 2030 offers an opportunity for developing sustainable management, in which the Pohorje destination acts in concert with the protected area. The public communication system and an efficient point of- sale network under the "From Pohorje" trademark can convince stakeholders that investments in the pastures and activities related to them not only pay off but also have a significant multiplier effect.
Keywords: doživljanje; kvaliteta; naravni viri; pašniki; Pohorje; Slovenia; Slovenija; turistična ponudba